THE EFFECT OF RAP (READ, ASK, PARAPHRASE) STRATEGY ON STUDENTS’ READING COMPREHENSION IN READING ANALYTICAL EXPOSITION TEXT - Veronika N.; Lince Sihombing (Universitas Negeri Medan, 2015)
This study focused on finding out the effect of applying RAP (Read, Ask,Paraphrase) Strategy on students’ reading comprehension in reading analyticalexposition text. This study was conducted in experimental design. The populationof this research was the second year of students in SMA Swasta Katolik BudiMurni 2 Medan. There were seventy students of the second year senior highschool students as the sample of the research. This study was conducted with tworandomized groups namely Experimental Group and Control Group. Theexperimental group was taught by applying RAP Strategy, while the control groupwas taught by applying conventional strategy. The instrument of collecting thedata was multiple choice tests which consisted of 25 items. The data wereanalyzed by using t-test formula. The calculation shown that t-observed (5.36)was higher than t-table (1.994) at the level of significance (α) 0.05 with the degreeof freedom (df) 68. It means that there was a significant effect of applying RAPStrategy on students’ reading comprehension in reading analytical exposition text.